Revision of EBC Method 4.12 for Diastatic Power (DP): Submitted on behalf of the Analysis Committee of the European Brewery Convention - Home, S.; Sharpe, R. (BrewingScience, 2007)
This method for Diastatic Power has been revised to correct an error in the equation for conversion between DP (WK) and DP (°IoB) that had previously been published in IoB method 2.7 (January 1997). It is an important change because a close study of some inter-laboratory ring check schemes revealed that some laboratories were using the equation quoted in the recommended methods to convert, some were using their own correct conversion and others were measuring by both analytical methods without conversion equations. This led to a greater spread of DP results between laboratories and some laboratories with a 10 % offset to others.